Maneuverability of Ships with small Draught in Steady Wind - Paroka, Daeng; Muhammad, Andi Haris; Asri, Syamsul (Makara Journal of Technology, 2016)
Wind force and moment may force a ship to drastically decrease its speed and use a large drift angle as well as a large rudder angle in order to maintain its course. Ships with a small draught might have more risk in maneuvering to its point of view compared with a ship with a larger draught. This paper discusses maneuverability of a ship with a small draught in steady wind. The effect of wind on ship speed, drift angle, and rudder angle are investigated in a steady state condition. Five different ratios of wind velocity to ship speed from 1.0 to 20.0 are used in the simulation. The variation in wind direction is examined from 0° to 180°. Results of the numerical simulation show that the wind has a significant effect on the reduction in ship speed with a wind direction less than 100°. The drift angle increases due to increasing wind velocity in the same wind direction. Wind direction also has a significant effect on the drift angle especially when the wind direction is less than 140°. The same phenomenon was found for the rudder angle. The necessary rudder angle is greater than the maximum rudder angle of the ship when the wind direction is 60° with a wind velocity to ship speed ratio of 20 or more.